Are Sunflower chlorotic mottle virus infection symptoms modulated by early increases in leaf sugar concentration? - Rodríguez, Marianela; Taleisnik, Edith; Lenardon, Sergio; Lascano, Ramiro (Journal of plant physiology, 2010)
Symptom development in a susceptible sunflower line inoculated with Sunflower chlorotic mottle virus (SuCMoV) was followed in the second pair of leaves at different post-inoculation times: before symptom expression (BS), at early (ES) and late (LS) symptom expression. Sugar and starch increases and photoinhibition were observed as early effects BS, and were maintained or enhanced later on, however, chlorophyll loss was detected only at LS. Photoinhibition correlated with a drastic decrease in D1 protein level. The progress of infection was accompanied by decreasing levels of apoplastic reactive oxygen species (ROS). In infected leaves, higher antioxidant enzyme activities (superoxide dismutase, SOD; ascorbate peroxidase, APX; glutathione reductase, GR) were observed from BS. The purpose of this work was to evaluate whether the early increases in carbohydrate accumulation may participate in SuCMoV symptom expression. Similar effects on photoinhibition, apoplastic ROS generation and antioxidant activity were generated when healthy leaves were treated with sugars. These results suggest that photoinhibitory processes and lower apoplastic superoxide levels induced by SuCMoV infection may be modulated by sugar increases.